The Concept of Islamic Storytelling for Phase A PAI Teachers - Bairanti Asriandhini; Ahmad Sastra; Wido Supraha (al-Afkar, Journal For Islamic Studies, 2023)
The reality that is happening in Indonesia is that Al-Qur'an stories have not become the mainstream in education both in terms of the quantity of stories that are narrated as well as in terms of quality, namely the concept of Islamic storytelling that is applied when telling or teaching about stories Al-Qur'an. This study aims to analyze the concept of Islamic storytelling which can be a practical guide for PAI teachers in phase A. The method used is maudhu'i interpretation and literature review. From this study, 3 important aspects were obtained which became the guide/concept of Islamic storytelling for phase A teachers. The first concept is the necessity of maintaining the truth of the story, the second is the obligation to maintain the objectives of the Al-Qur'an story which are aligned with the characteristics of phase A, and the third It is imperative for every teacher to maintain and always improve moral and religious competence as well as build closeness with students.